1976
DOI: 10.1002/jez.1401950112
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood PH, ammonia excretion and adaptation to low salinity in the blue crab callinectes sapidus

Abstract: b l u e crabs absorb Na a g a i n s t a gradient, b u t n o t those i n which crabs remain i n s a l t balance w i t h t h e medium. Net a c i d o u t p u t does n o t c l e a r l y vary w i t h s a l i n i t y . The balance between ammonia and urea o u tp u t s h i f t s towards ammonotelism a t : ow s a l i n i t y . These r e s u l t s , and the temporal responses o f b l o o d NH change, support the hypothesis tha? excess ammonia i n b l o o d p l a y s an i m p o r t a n t r o l e i n osmoregulation as w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 11 publications
1
41
0
3
Order By: Relevance
“…However, under simulated tidal conditions close to our own, Armitage and Morris (1982) did not observe any significant changes in amino-acid concentrations over the ebb phase nor the flood phase of the cycle. On the other hand, it was demonstrated that the active sodium uptake following the transfer into a hypotonic medium was related to an increased ammonia output (Mangum et al, 1976;Pressley et al, 1981). By contrast, a reduction of the Na+/NH4+ exchanges (Pequeux and Gilles, 1981) and a possible reversal of these exchanges (Armstrong et al, 1981) were observed following transfer into a hypertonic medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under simulated tidal conditions close to our own, Armitage and Morris (1982) did not observe any significant changes in amino-acid concentrations over the ebb phase nor the flood phase of the cycle. On the other hand, it was demonstrated that the active sodium uptake following the transfer into a hypotonic medium was related to an increased ammonia output (Mangum et al, 1976;Pressley et al, 1981). By contrast, a reduction of the Na+/NH4+ exchanges (Pequeux and Gilles, 1981) and a possible reversal of these exchanges (Armstrong et al, 1981) were observed following transfer into a hypertonic medium.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with this, significant changes in ammonia excretion rate were observed in crustaceans (Needham, 1957;Haberfield et al, 1975;Mangum et al, 1976;Farmer and Reeve, 1978;Armstrong et al, 1981;Pressley et al, 1981;Spaargaren et al, 1982). However, the salinity effect on nitrogen excretion was dependent on the species and its osmoregulatory abilities.…”
Section: Introductionmentioning
confidence: 97%
“…Mangum et al, 1976); posterior gills contain osmoregulatory structures (e.g. Copeland and Fitzjarrell, 1968;Gilles et al, 1988;Péqueux, 1995) and constitute the important ion-regulating organs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen metabolism and the role of FAA in the regulation of intracellular osmolarity and volume regulation have been widely studied and reviewed by Claybrook (1983) and Gilles & Pequeux (1983). Several studies have reported an increase of ammonia excretion and a spontaneous decrease of tissue FAA when crustaceans are exposed to hypo-osmotic conditions (Haberfield et al 1975, Mangum et al 1976). Effects of salinity on FAA composition have been examined for Kuruma shrimp Penaeus japonicus by Dalla Via (1986) and for P. monodon by Fang et al (1992).…”
Section: Introductionmentioning
confidence: 99%